The role calibration ruler in Endodontics (LLC "Endo Press", 2020)
In the article shows the comparative results of the study of dental instruments of diff erent companies on the stages of the passage of the root canal, drying, obturation guttapercha point. In all companies were found a large number of endodontic instruments does not match the size of the calibration ruler. The standardized guttapercha point with conicity 02 also didn't correspond to the declared size of an endodontic rule. The revealed discrepancy of the size of a guttapercha point considerably exceeds its admissible deviation fi rm the producer. It reduces quality of endodontic treatment: worsens quality of adhesion of sealing material to walls of the root channel and increases probability of penetration of a secondary infection. Therefore for a dense obturation of the lower third of the root channel it is necessary to carry out calibration of gutta-percha pins by means of the endodontic ruler.